A Reinterpretation of the Cytoarchitectonics of the Telencephalon of the Comoran Coelacanth - Northcutt, R. Glenn; González, Agustín (Frontiers in Neuroanatomy, 2011)
The cytoarchitecture of the telencephalon of the Comoran coelacanth, Latimeria chalumnae, was analyzed in the context of recent advances in our understanding of telencephalic organization in lungfishes and amphibians, which constitute the sister group to coelacanths. In coelacanths, the telencephalon is divided into pendunculated olfactory bulbs, paired hemispheres, and an unevaginated telencephalon impar. The hemispheres consist of a ventrally located subpallium and, dorsally, a greatly expanded pallium. Traditionally, the subpallium in coelacanths has been divided into a medial septal area and a lateral striatum. Re-examination of the lateral subpallial wall, however, suggests that the striatum is more restricted than previously believed, and it is replaced dorsally by a more scattered plate of cells, which appears to represent the ventral pallium. The putative ventral pallium is continuous with a ventromedial pallial formation, which appears to receive input from the lateral olfactory tract and should be considered a possible homologue of the lateral pallium in tetrapods. The putative lateral pallium is replaced by a more dorsomedial pallial formation, which may represent the dorsal pallium. This formation is replaced, in turn by an extensive lateral pallial formation, which appears to be homologous to the medial pallium of tetrapods. An expanded medial pallium in coelacanths, lepidosirenid lungfishes, and amphibians may be related to well developed spatial learning. Traditionally, the telencephalon impar of coelacanths, has been interpreted as an enlarged preoptic area, but reanalysis indicates that the so-called superior preoptic nucleus actually consists of the medial amygdalar nucleus.